Roots Quantity of Maxillary Wisdom Teeth of Libyan Subpopulation at Zliten City Using CBCT: A Retrospective Study - A Alaali Ehbesh; Ahmed Alteer; Mohamed Attir (AlQalam Journal of Medical and Applied Sciences, 2025)
This study aims to evaluate the number of roots of maxillary wisdom teeth of the Libyan subpopulation at Zliten city, to compare incidences in different side locations, and to compare the prevalence of root number in both genders. This was a retrospective study showing 806 CBCT images met the inclusion criteria out of 2078 CBCT images (X-MIND Prime®3D- Acteon software) that had been collected from Al-Tasneem Private Poly-clinics at Zliten city in Libya over the period from January 2024 to May 2025. 55.7% (425 CBCT images) were right-sided, while 53.6% (432 CBCT images) were female. The highest root numbers of maxillary wisdom teeth in the Libyan subpopulation at Zliten city were three rooted teeth with 80.02%, while the lowest incidences were four rooted teeth with 2.61%. The incidences of three-rooted teeth were slightly higher on the right side than on the left side, with 80.9% and 79% respectively. However, the incidences of three-rooted teeth were higher in females than in males, with 82.4% and 78% respectively. The prevalence of one-rooted teeth was higher in males than in females. The frequencies of two and four-rooted teeth were almost equal in both genders. The number in the current study ranged from 1 to 4 roots. The highest root numbers of incidences of maxillary wisdom teeth in the Libyan subpopulation at Zliten city were three rooted teeth. The most frequent total bilateral root number in the current study was in three rooted teeth, with 25.9%.